2017
DOI: 10.3390/mi8030081
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Effect of Process Variations on a Micromachined Doubly-Clamped Beam

Abstract: In the fabrication of micro-electro-mechanical systems (MEMS) devices, manufacturing process variations are usually involved. For these devices sensitive to process variations such as doubly-clamped beams, mismatches between designs and final products will exist. As a result, it underlies yield problems and will be determined by design parameter ranges and distribution functions. Topographical changes constitute process variations, such as inclination, over-etching, and undulating sidewalls in the Bosch proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Different thermal expansions and geometries generate thermal stresses that vary along layer films and depend on the material properties, e.g., the Young’s moduli, the coefficients of thermal expansion, the thermal conductivity, etc. Also in [ 24 ], the scholars reached a similar conclusion: when manufacturing MEMS, the manufacturing process variations led to mismatches between the original designs and the final products.…”
Section: Memscap ® Actuatormentioning
confidence: 85%
“…Different thermal expansions and geometries generate thermal stresses that vary along layer films and depend on the material properties, e.g., the Young’s moduli, the coefficients of thermal expansion, the thermal conductivity, etc. Also in [ 24 ], the scholars reached a similar conclusion: when manufacturing MEMS, the manufacturing process variations led to mismatches between the original designs and the final products.…”
Section: Memscap ® Actuatormentioning
confidence: 85%
“…Like perturbation methods, they are also restricted to small uncertainties [ 25 ] and strongly dependent on the underlying operators. We previously developed adequate processing models to predict the device performance [ 26 ]. However, these approaches are not applicable to complex device models with different process deviation distributions.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Quality control of micro systems and processes. Baruffi et al [7] demonstrated the application of the replica molding technology for quality control of micro milled surfaces; Cao et al [8] investigated the effect of profile errors on the surface of micro lenses on laser beam homogenization; Choi et al [9] presented a novel testing platform to characterize and predict the mechanical damage of miniaturized haptic actuator; Gao et al [10] modeled the effect of micro manufacturing process variations on the characteristics of a micro machined doubly-clamped beam.…”
mentioning
confidence: 99%